高齢パーキンソン病に対するソフトロボットグローブを使用した遠隔監視による在宅作業療法—実行可能性に関する予備的事例研究 - 加賀山 俊平; 園田 悠馬; 多賀 優佳 (作業療法, 2024)
要旨：本研究は在宅生活を送るパーキンソン病（以下，PD）患者におけるロボットグローブ（以下，RG）を用いた遠隔監視下の作業療法（以下，OT）の実行性と認容性，ならびに上肢機能，Quality of Life，介護負担に対する有効性の探索を目的とした予備的事例研究である．RG装着と非装着のOTを順に各々週2回・5週間実施し，手の痛みや強い疲労と脱落，簡易上肢機能検査，カナダ作業遂行測定，EuroQol 5-dimension5-level，Zarit介護負担感尺度を6ヵ月間観察した．研究中に有害事象と欠席はなく，RG装着OT後に全評価項目で改善を認めたが，RG非装着で低下し20週後にRG装着前と同等になった．本OTは実行性・認容性・有効性が確認され，在宅PD患者に対するOTの1つとして検討され得る． 　This study aimed to explore the feasibility and tolerability of remote-monitored occupational therapy (OT) using robotic gloves (RG) in home-dwelling patients with Parkinson's disease( PD) and its effectiveness on upper extremity function, health-related quality of life, and caregiver burden. This is a preliminary single-case study of OT with and without RG performed twice a week for five weeks. Hand pain and severe fatigue, dropouts, simple test for evaluating hand function, Canadian Occupational Performance Measure, EuroQol 5-dimension 5-level, and Zarit burden interview were observed for six months. During the study, there were no adverse events or absences. All outcomes improved after OT with RG but declined gradually without RG, returning scores comparable to pre-OT with RG after six months. This OT program for home-dwelling patients with PD has been confirmed to be feasible, tolerable, and effective, and may be considered a future home OT.